Integration of GIS and TM Data in Extraction of Early Rice Planted Area of South of China: A Case Study of Longyou County - Ahmad Yaghi; HUANG Jing-feng; WANG Ren-chao; Abou-Ismail Ousama; Al-Abed Mohammad (浙江大学学报. 农业与生命科学版)
This paper introduced the methodology of early rice planted area estimation by integration of GIS and TM data. The methodology enhanced the classification precision of TM image in both plain and mountainous areas. Land-use and town boundary maps were digitized and transferred to raster format and opened in ENVI image analysis system. TM image, land use map and town boundary map were registered at the same projection. Utilizing the mask function in ENVI image analysis system, the study area, different land use types and towns TM images were established. The early rice planted area was calculated from Longyou TM image and paddy field TM image using supervised classification methods. Application of Maximum likelihood and Parallelepiped methods on TM image for early rice area estimation enabled the achievement of 59.95% and 82.83% classification precision, whereas applying the same methods on paddy field TM image enhanced the classification precision up to 60.65% and 93.98% respectively. Thus, in this study, Parallelepiped method applied to paddy field TM image was proposed as the best method for early rice area estimation in Longyou County. In addition the early rice information derived from this methodology can be used in any rice-monitoring model or yield estimation studies with high accuracy and less susceptibility to error. The availability of GIS database makes the method easily applicable to new TM images.